Identification of Functional and Expression Polymorphisms Associated With Risk for Antineutrophil Cytoplasmic Autoantibody–Associated Vasculitis. Issue 5 (6th April 2017) - Merkel, Peter A.; Xie, Gang; Monach, Paul A.; Ji, Xuemei; Ciavatta, Dominic J.; Byun, Jinyoung; Pinder, Benjamin D.; Zhao, Ai; Zhang, Jinyi; Tadesse, Yohannes; Qian, David; Weirauch, Matthew; et al.
Abstract : Objective: To identify risk alleles relevant to the causal and biologic mechanisms of antineutrophil cytoplasmic antibody (ANCA)–associated vasculitis (AAV). Methods: A genome‐wide association study and subsequent replication study were conducted in a total cohort of 1, 986 cases of AAV (patients with granulomatosis with polyangiitis [Wegener's] [GPA] or microscopic polyangiitis [MPA]) and 4, 723 healthy controls. Meta‐analysis of these data sets and functional annotation of identified risk loci were performed, and candidate disease variants with unknown functional effects were investigated for their impact on gene expression and/or protein function. Results: Among the genome‐wide significant associations identified, the largest effect on risk of AAV came from the single‐nucleotide polymorphism variants rs141530233 and rs1042169 at the HLA–DPB1 locus (odds ratio [OR] 2.99 and OR 2.82, respectively) which, together with a third variant, rs386699872, constitute a triallelic risk haplotype associated with reduced expression of the HLA–DPB1 gene and HLA–DP protein in B cells and monocytes and with increased frequency of complementary proteinase 3 (PR3)–reactive T cells relative to that in carriers of the protective haplotype. Significant associations were also observed at the SERPINA1 and PTPN22 loci, the peak signals arising from functionally relevant missense variants, and at PRTN3, in which the top‐scoring variant correlated with increased PRTN3 expression in neutrophils. Effects of individual loci on AAV risk differed between patients with GPA and those with MPA or between patients with PR3‐ANCAs and those with myeloperoxidase‐ANCAs, but the collective population attributable fraction for these variants was substantive, at 77%. Conclusion: This study reveals the association of susceptibility to GPA and MPA with functional gene variants that explain much of the genetic etiology of AAV, could influence and possibly be predictors of the clinical presentation, and appear to alter immune cell proteins and responses likely to be key factors in the pathogenesis of AAV.